Health conditions that predict Alzheimer's disease and vascular dementia: A phenome‐disease association study. (31st December 2021) - Beason‐Held, Lori L; Kerley, Cailey I; Chaganti, Shikha; Moghekar, Abhay; Thambisetty, Madhav; Resnick, Susan M; Landman, Bennett A
Abstract: Background: Poor health increases the risk of cognitive decline and dementia. Here, we examined medical records to determine health conditions that were most predictive of dementia at intervals prior to dementia diagnosis. This phenome‐disease association study (PheDAS) used ICD‐9 health code medical record data from participants in the Baltimore Longitudinal Study of Aging (BLSA). Methods: Data were available for 347 Alzheimer's disease (AD), 76 vascular dementia (VD), and 811 non‐demented control participants. Logistic regressions were performed associating ICD‐9 health codes with dementia status at 5 and 1 year(s) prior to dementia diagnosis and at the year of diagnosis, controlling for maximum age, sex and follow‐up length of medical record. Results: In AD, the earliest and most consistent predictors across all time points included depression, erectile dysfunction, gait abnormalities, hearing loss, and nervous and musculoskeletal symptoms. Cardiomegaly, disorders of esophageal motility and non‐epithelial skin cancer were not significant until 1 year before dementia diagnosis. In VD, the earliest and most consistent predictors across all time points included abnormal EKG, cardiac dysrhythmias, cerebrovascular disease, non‐epithelial skin cancer, depression, and hearing loss. Atrial fibrillation, occlusion of cerebral arteries, and abnormal reflexes were not significant until 1 year before dementia diagnosis. Conclusions: These findings suggest that some health predictors of future dementia begin at least 5 years before dementia diagnosis and are consistently seen over time, while others only reach significance closer to the date of diagnosis. These results also show that there are both shared and distinctive health predictors for AD and VD. Together, this study reinforces the need for proper care and treatment of modifiable health risk factors throughout the lifespan. This work was supported by the Intramural Research Program of the NIH, National Institute on Aging.